Socio-Religious Resilience and Indigenous Identity in the Cireundeu Community, Cimahi - Muhammad Alfan; Asep Saeful Mimbar; Busro Busro (Lembaga Bale Literasi, 2026)
This study examines the socio-religious resilience of the Cireundeu indigenous community in Cimahi, West Java, in preserving ancestral values, local spirituality, and interfaith cohesion amid urban modernization. While previous studies have discussed indigenous adat (customary tradition), local belief systems, interfaith harmony, and cultural tourism separately, limited attention has been given to how these dimensions operate together as an integrated mechanism of resilience within an urban indigenous community. Using a qualitative case study approach within the anthropology of religion, this study draws on in-depth interviews, field observations, visual documentation, and document analysis. The data were analyzed thematically by focusing on interfaith solidarity, Sunda Wiwitan/Agama Djawa Sunda (ancestral Sundanese belief/ADS) spirituality, customary values, sacred spaces, food-based identity, ritual practices, and adaptation to modernization. The findings show that Cireundeu’s resilience is shaped through three interrelated processes. First, interfaith harmony is sustained through kinship ties, gotong royong (mutual cooperation), mutual participation in Islamic celebrations and Seren Taun (annual thanksgiving and ancestral ritual), and respect for sacred communal spaces such as mosques and paseban (customary communal hall). Second, ancestral values are preserved through Sunda Wiwitan/ADS, Pikukuh Tilu (three firm principles), Tri Tangtu (threefold order), rasi (cassava-based rice) as a food-based identity, ecological ethics, and ritual continuity. Third, modernization is negotiated through the principle of Ngindung Ka Waktu, Mibapa Ka Jaman (following the times while preserving inherited identity), which enables selective adaptation without abandoning indigenous identity. This study argues that Cireundeu’s resilience should not be understood as cultural isolation, but as an everyday socio-religious process formed through negotiation, participation, symbolic continuity, and adaptive engagement with urban change.